Primary Tuberculosis of the Chest Wall Without Pulmonary Involvement: A Case Report - Priyadarshini S. Nayak; Ranjith K. Bhaskar; Gopinath Pai; S. Chandrashekar (Medical Journal of Dr. D.Y. Patil Vidyapeeth)
Chest wall tuberculosis (TB) is often associated with primary pulmonary TB. Primary chest wall TB without any pulmonary involvement is a rare form of musculoskeletal TB and is relatively difficult to diagnose due to nonspecific symptoms. Without significant clinical indications, accepting the possibility of a tubercular origin in chest wall tuberculosis can be challenging, which can mimic a pyogenic abscess or tumor. To rule out potential mycobacterial causes, all abscesses in tuberculosis-endemic areas like India that are resistant to standard therapy must be investigated. Herein, we present a case of primary tuberculosis of the chest wall, which was treated successfully.